2017
DOI: 10.1080/09537104.2016.1257784
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating platelet function disorders in children with bleeding tendency – A single center study

Abstract: Platelet function disorders (PFDs) are a common cause of mild bleeding tendency. However, they cannot be recognized by standard screening studies. The gold standard test for PFD is platelet aggregation, performed by light transmission aggregometry (LTA). A newer and less validated method is the closure time (CT), performed by the platelet function Analyzer 100 (PFA-100). Data regarding the validity of these tests in children are limited. The aim of this study was to evaluate the usefulness of LTA and PFA-100 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…However, our study unexpectedly observed that ADP in the defervescence period of KD was slightly prolonged compared with that in the febrile period of KD or that in the defervescence period of the febrile control group. Except for other factors, such as the reduced hematocrit or platelet count 25 , it indicates that IVIG can inhibit platelet activation in KD patients, as reported in previous studies 26,27 .…”
Section: Discussionsupporting
confidence: 74%
“…However, our study unexpectedly observed that ADP in the defervescence period of KD was slightly prolonged compared with that in the febrile period of KD or that in the defervescence period of the febrile control group. Except for other factors, such as the reduced hematocrit or platelet count 25 , it indicates that IVIG can inhibit platelet activation in KD patients, as reported in previous studies 26,27 .…”
Section: Discussionsupporting
confidence: 74%
“…Platelet dysfunction or acquired von Willebrand syndrome may result from blood circulation through mechanical circuitry (such as CPB, ECMO, ventricular assist devices, or hemofiltration), renal failure, or pharmacologic agents (such as antiplatelet agents, nonsteroidal anti-inflammatories, or milrinone) (37). Platelet aggregation studies may provide additional information in children who are at high risk of bleeding from platelet dysfunction; in those children, total platelet count should not be the sole indication for platelet transfusion (38). Clinicians must consider the etiology of the thrombocytopenia and/ or coagulopathy when deciding to transfuse.…”
Section: Discussionmentioning
confidence: 99%
“…Citrated whole blood is applied to a test cartridge that contains a collagen-coated membrane and either epinephrine (Col/Epi) or adenosine diphosphate (Col/ADP). 2,3 The PFA-200 has been used to detect acquired and congenital platelet dysfunctions 4,5 and to screen for von Willebrand disease (vWD) in adults. The 2 test cartridge system was developed to differentiate between the effects of nonsteroidal anti-inflammatory drugs 6,7 and other types of qualitative defects in platelets.…”
Section: Comparison Between Bleeding Time and Pfa-200 To Evaluate Pla...mentioning
confidence: 99%